2021
DOI: 10.3889/oamjms.2021.6114
|View full text |Cite
|
Sign up to set email alerts
|

Composite Bacterial Infection Index and Serum Amyloid A Protein in Pulmonary Tuberculosis Patients and their Household Contacts in Makassar

Abstract: BACKGROUND: Early diagnosis of tuberculosis (TB) cases in limited resource remains challenging. It is urgent to identify the new diagnostic tools which can control the spread of disease with accurate and rapid test. AIM: This study aimed to investigate the levels of infection markers: Composite bacterial infection index (CBII) and serum amyloid A (SAA) protein in pulmonary TB (PTB), and their healthy household contacts, as the alternative diagnostic markers for TB. METHODS: CBII and SAA were measured from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[36][37][38][39] Findings from earlier studies in adults have also shown the association of higher ratios in TB disease when compared to healthy controls. [15][16][17][18][20][21][22][23][40][41][42][43][44][45][46] One study from Spain including 60 adults (21 with TB disease, 19 with TB infection and 20 healthy TB exposed) reported a sensitivity of 77% and a specificity of 81% (cutoff of 2.85 and AUC of 0.83) to classify patients with TB disease versus exposed uninfected individuals. 40 Another study from Turkey including 134 adults (51 with TB disease, 40 with sarcoidosis and 43 controls) reported a sensitivity of NLR of 88% and a specificity of 80% (cutoff of 2.16 and AUC of 0.92) to classify patients with TB disease versus controls.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] Findings from earlier studies in adults have also shown the association of higher ratios in TB disease when compared to healthy controls. [15][16][17][18][20][21][22][23][40][41][42][43][44][45][46] One study from Spain including 60 adults (21 with TB disease, 19 with TB infection and 20 healthy TB exposed) reported a sensitivity of 77% and a specificity of 81% (cutoff of 2.85 and AUC of 0.83) to classify patients with TB disease versus exposed uninfected individuals. 40 Another study from Turkey including 134 adults (51 with TB disease, 40 with sarcoidosis and 43 controls) reported a sensitivity of NLR of 88% and a specificity of 80% (cutoff of 2.16 and AUC of 0.92) to classify patients with TB disease versus controls.…”
Section: Discussionmentioning
confidence: 99%